2016
DOI: 10.1007/s00277-016-2729-4
|View full text |Cite
|
Sign up to set email alerts
|

The different roles of molecular classification according to upfront autologous stem cell transplantation in advanced-stage diffuse large B cell lymphoma patients with elevated serum lactate dehydrogenase

Abstract: The non-germinal center B cell (non-GCB) subtype of diffuse large B cell lymphoma (DLBCL) is more related to poor prognosis than the GCB subtype. To investigate the role of molecular classification according to upfront autologous hematopoietic stem cell transplantation (ASCT), we retrospectively evaluated 219 newly diagnosed high-risk DLBCL patients. Eighty-one patients were in the ASCT group, and 138 patients were in the non-ASCT group. The ASCT group yielded significantly better overall survival (OS) and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
(39 reference statements)
1
13
0
1
Order By: Relevance
“…Thus, miR-BHRF1-1 may contribute to cell adhesion, proliferation, and motility of EBV-infected B cells in response to LA. Consistent with previous observations in many cancers (9,24,25), LDH was elevated in B cells by EBV infection and in EBV-positive B-cell lymphoma cells. However, previous studies suggest that EBV encodes LMP1 to upregulate anaerobic glycolysis (20,21) and c-myc induces LDH-A expression (26), but whether EBV upregulates c-Myc to induce LDH-A expression or is directly induced by LMP1 is not clear.…”
supporting
confidence: 92%
“…Thus, miR-BHRF1-1 may contribute to cell adhesion, proliferation, and motility of EBV-infected B cells in response to LA. Consistent with previous observations in many cancers (9,24,25), LDH was elevated in B cells by EBV infection and in EBV-positive B-cell lymphoma cells. However, previous studies suggest that EBV encodes LMP1 to upregulate anaerobic glycolysis (20,21) and c-myc induces LDH-A expression (26), but whether EBV upregulates c-Myc to induce LDH-A expression or is directly induced by LMP1 is not clear.…”
supporting
confidence: 92%
“…In the overall cohort, relapses were reported in 15 of 72 patients Median days to leukocytes ≥1.0×10 9 /L (range) 11 (7-32) 11 (7-16) 12 .682 11 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) 12 (9-16) 11 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) .379…”
Section: Impact Of Upfront Versus Secondary Hdt/ Absct On Survivalmentioning
confidence: 99%
“…However, the better outcome could be explained by a better risk profile because low and low-intermediate IPI risk patients were also included in the current study. Furthermore, the comparability is hampered by the difference in control groups, which include patients who received the secondary HDT/ABSCT in the current analysis and standard induction treatment in the studies performed by Stiff et al and Kim et al18,20 Moreover, it should be considered that 13 patients with DLBCL who participated in the multicenter, prospective, randomized HD2002 trial, which is not a standard of care and might contribute to a beneficial outcome. Overall, the results obtained in the current study correlate with the previously reported data and contribute to the scarce amount of data on this topic.…”
mentioning
confidence: 99%
“…A phase II study performed by Vitolo et al (2009) compared the addition of rituximab to HDT/ASCT to those without rituximab in patients with untreated, IPI high-intermediate/high-risks DLBCL and found 4-year OS were 80% and 54%, respectively [24]. Kim et al (2016) published a retrospective study to assess the effect of upfront ASCT in patients with advance-stage DLBCL of different molecular classification (GCB versus non-GCB) and found significant OS and PFS benefits within the ASCT group compared to the non-ASCT group [25]. In the non-ASCT group, patients had poorer outcome in the non-GCB subtype while there were no significant differences between the two subtypes in the ASCT group.…”
Section: Introductionmentioning
confidence: 99%